Determinants Affecting Student’s Performance in Teaching Physiology: A retrospective analysis (Anwer Khan Modern Medical College Journal, 2023)
Background: This was a descriptive cross-sectional study among the students in the department of physiology at Khwaja Yunus Ali Medical College (KYAMC) during the period of December 2019 – January 2020 using a structured questionnaire and a checklist for record review of 1st professional examination results.Objectives: To find out number of determinants including socio-demographic characteristics affecting student’s performance in teaching physiology course in addition to the perceived factors for better performance.Methods: The data were generated from using a structured questionnaire and a checklist for retrospective record review of 1st professional examination results where the sampling technique was purposive / convenient in nature, the respondents willing to participate. It was analyzed manually & by computer program as appropriate.Results: In this study among the total 52.57% respondents were male and 47.43% were female where 93.59% were within 20-22 years of age and 97.44% were Muslim by religion. The choice of respondent’s profession was by 25.64% parents. Only 47% and 67% respondents had regular exercise & enough sleep habits. Choice of foods in daily diet as fruits & vegetables were found adequate to only 35-50% respondents, and as milk and yogurt to 35-40% only. Listening music, playing games, using internet, capture photos, sending mails & text including sending and receiving calls were the most pattern of cell phone use among 75-98% respondents. Unbiased behavior of teachers, physical environment of class room, library facilities, available books in the library, adequate opportunities for internet & photo copy, and consideration of student’s opinion in teaching and learning were identified as perceived factors towards better performance to about 35-65% respondents.Conclusion: Scope for regular exercise and dietary inclusion of fruits & vegetables needs emphasizing in addition to consumption of milk and yogurt. Opportunities for class room facilities, book in the library, internet & photocopy needs to be created further. Student’s opinion in teaching learning process may also be considered towards better academic performance. Unbiased teacher’s behavior can be an added input in this direction as well.AKMMC J 2021; 12(1) : 22-27